The recovery of the LGBTIQ+ memory prior to Pride through documentary film: La memoria homosexual as a case study (Anclajes, 2024)
The repression of sexual diversity prior to the advent of Pride is the subject of a growing number of documentary films released in the second decade of the 21st century, including Espino Diéguez’s La memoria homosexual (Homosexual Memory) (2019). An analysis of this documentary as a case study reveals that the enunciative strategies of the documentary genre are suitable for the recovery of a queer audiovisual memory capable of rescuing experiences of shame and oppression from perspectives more clearly aligned with Pride. This kind of recovery of historical memory casts a double temporality as the narrative of memorialized experiences is determined by discursive premises that belong to the present historical moment – a time in which a hegemonic democratic memory coexists with the hypernormalization of sexual diversity.
Keywords: Cultural memory; Documentary film; LGBT community; Pride; Homophobia